Estimating microbial growth and hydrogen consumption in hydrogen storage in porous media. (November 2021) - Thaysen, Eike M.; McMahon, Sean; Strobel, Gion J.; Butler, Ian B.; Ngwenya, Bryne T.; Heinemann, Niklas; Wilkinson, Mark; Hassanpouryouzband, Aliakbar; McDermott, Christopher I.; Edlmann, Katriona
Abstract: Subsurface storage of hydrogen, e.g. in depleted oil and gas fields (DOGF), is suggested as a means to overcome imbalances between supply and demand in the renewable energy sector. However, hydrogen is an electron donor for subsurface microbial processes, which may have important implications for hydrogen recovery, gas injectivity and corrosion. Here, we review the controls on the three major hydrogen consuming processes in the subsurface, methanogenesis, homoacetogenesis, and sulfate reduction, as a basis to estimate the risk for microbial growth in geological hydrogen storage. Evaluating our data on 42 DOGF showed that five of the fields may be considered sterile with respect to hydrogen-consuming microorganisms due to temperatures >122 °C. Only six DOGF can sustain all of the hydrogen consuming processes, due to either temperature, salinity or pressure constraints in the remaining fields. We calculated a potential microbial growth in the order of 1–17*10 7 cells ml −1 for DOGF with favorable conditions for microbial growth, reached after 0.1–19 days for growing cells and 0.2–6.6 years for resting cells. The associated hydrogen consumption is negligible to small (<0.01–3.2% of the stored hydrogen). Our results can help inform decisions about where hydrogen will be stored in the future. Graphical abstract: Image 1 Highlights: Review of the most important hydrogen-oxidizing microorganisms in the underground. Elucidation of the growth criteria for 518 strains of the major hydrogen-oxidizers. Screening of 42 depleted oil and gas fields (DOGF) for possible microbial growth. Calculation of the microbial growth and hydrogen consumption in DOGF.